Parents' Participation Experiences In Care Of Stunting Children In The Middle Of The Covid-19 Pandemic In Laha Village, District Ambon Bay Ambon City - Asih Dwi Astuti (Sean Institute, 2023)
Stunting (dwarf / short) is a condition that inhibits growth and development in toddlers. Parents have an important role in caring for children with stunting by routinely checking at the Posyandu. The purpose of the study was to identify the experience of parents in caring for children with stunting in the midst of the Covid-19 pandemic in Laha Village, Teluk Ambon District, Ambon City. This type of research is qualitative with the interview method. The informants of this study were the parents of children suffering from stunting. The results showed that most of the informants said that they came to the posyandu to weigh and measure TB, most of the informants said they had difficulty bringing children to the posyandu by wearing masks and avoiding crowds, while 1 out of 7 informants did not come to the posyandu because children were susceptible to being exposed to Covid-19. 19. All of the informants said that in order for children to be monitored for their growth, to receive stunting treatment, to know the lack of children and parenting patterns, almost all of the informants said that in monitoring the growth of children, they had to take their children to the posyandu in order to find out their weight and TB. Only 1 out of 7 mothers bought a TB and BB measuring device. All informants said that the obstacle they experienced was the absence of a tool to measure TB and BB. All of the informants said that the children got enough food, but the fulfillment of protein from fish was still rarely given. Based on the results of the study, most of the informants continued to come to the posyandu, almost all of the informants monitored the growth of children at the posyandu in order to find out their weight and TB, and all of the informants said that the children got enough food. Further research is expected so that informants can provide information in Indonesian so that readers can better understand.